West Germany and the global sixties : the antiauthoritarian revolt, 1962-1978 - Brown, Timothy Scott 1961- (New studies in European history, 2013)
"The anti-authoritarian revolt of the 1960s and 1970s was a watershed in the history of the Federal Republic of Germany. The rebellion of the so-called '68ers' - against cultural conformity and the ideological imperatives of the Cold War; against the American war in Vietnam; in favor of a more open accounting for the crimes of the Nazi era - helped to inspire a dialogue on democratization with profound effects on German society. Timothy Brown examines the unique synthesis of globalizing influences on West Germany to reveal how the presence of Third World students, imported pop culture from America and England and the influence of new political doctrines worldwide all helped to precipitate the revolt. The book explains how the events in West Germany grew out of a new interplay of radical politics and popular culture, even as they drew on principles of direct-democracy, self-organization and self-determination, all still highly relevant in the present day"--